Respuesta :

Answer:

X = C - By over A which also is A ≠ 0

Y = C - Ax over B which is also B ≠ 0

Step-by-step explanation:

Solve for x

First subtract "By" from both sides:

Ax + By - By = C - By

Then simplify,

Ax = C - By

Divide both sides by A:

Ax / A = C/A - By/A ; A≠0

Then simplify:

X = C - By over A ; A ≠ 0.

-------------------------------------

Solve for y

First subtract "Ax" from both sides:

Ax - By - Ax = C - Ax

Simplify,

By - C = Ax

Then divide both sides by B:

By/B = C/B - Ax/B ; B ≠ 0

Simplify:

Y = C-Ax / B ; B ≠ 0.

Hope this helps have a good day! :)

( This symbol '/' means a dash like a fraction btw same with the word over.)

Brainliest would be appreciated?